Open Reduction and Internal Fixation of Radial Head Fractures: Do Outcomes Differ Between Simple and Complex Injuries? - Pike, Jeffrey M. (Springer US, 2014)
BACKGROUND: Radial head fractures can occur in isolation or in association with elbow and forearm injuries. Treatment options include nonoperative management, fragment or whole-head excision, open reduction and internal fixation (ORIF), and radial head arthroplasty. However, the evidence supporting ORIF for repairable radial head fractures is inconclusive. QUESTIONS/PURPOSES: We compared patients undergoing ORIF for isolated radial head fractures or for radial head fractures associated with other fractures or elbow dislocations in terms of patient-related disability, presence of posttraumatic arthritis, complications, and rate of reoperation for capsular release. METHODS: Between 1997 and 2008, 52 patients underwent ORIF of the radial head for isolated radial head fractures (simple group) and 29 underwent ORIF for radial head fracture with an associated fracture or dislocation (complex group). General indications for ORIF included displaced radial fractures, large articular surface fragments, and greater than 2 mm of displacement and/or a mechanical block to forearm rotation or associated fractures or ligament injuries requiring surgery. Thirty-one patients (60%) in the simple group and 20 (69%) in the complex group were available for followup at a mean of 4 years (range, 1.0–9.5 years). We evaluated the patients using a validated self-reported pain and disability questionnaire (Patient-rated Elbow Evaluation [PREE]). Records review included radiographic examination and assessment of major complications and secondary surgery rates for capsular release. RESULTS: With the numbers available, the groups were not different in terms of the mean PREE scores (8 versus 15 for the simple and complex groups, respectively; p = 0.13, lower values indicate lower pain and disability). The simple and complex groups were also not different with the numbers available in terms of major complications (13% versus 25%, respectively; p = 0.29) or secondary capsular release (3% versus 20%, respectively; p = 0.07). CONCLUSIONS: At short term, we found no differences between patients treated with ORIF for isolated radial head fractures and those treated for radial head fractures in association with other elbow injuries with regard to pain and disability scores; loss to followup in this series precludes making statements with great confidence about function after these injuries. However, the substantial capsular release and complication rates should weigh into the preoperative discussion with patients before selecting ORIF for radial head fractures. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.